2020
DOI: 10.1007/s00426-020-01335-y
|View full text |Cite|
|
Sign up to set email alerts
|

Enhancing task-demands disrupts learning but enhances transfer gains in short-term task-switching training

Abstract: Content variability was previously suggested to promote stronger learning effects in cognitive training whereas less variability incurred transfer costs (Sabah et al. Psychological Research, 10.1007/s00426-018-1006-7, 2018). Here, we expanded these findings by additionally examining the role of learners’ control in short-term task-switching training by comparing voluntary task-switching to a yoked control forced task-switching condition. To this end, four training conditions were compared: (1) forced fixed con… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 61 publications
3
7
0
1
Order By: Relevance
“…Switch proportion effects could be mediated by task cue- or item-triggered priming of a context-sensitive control setting. This lack of transfer to other tasks also fits with cognitive training studies demonstrating that switch costs decrease over training when the same tasks are used, but substantial costs reemerge when participants are confronted with new tasks to switch between (Sabah et al, 2019, 2021). With respect to theories on relative levels of task-set activation, Siqi-Liu and Egner (2020) suggest that less activation (and shielding) of both task sets is more likely than increased activation of both task sets to explain the switch probability effect.…”
Section: Switching-induced Flexibilitysupporting
confidence: 74%
See 1 more Smart Citation
“…Switch proportion effects could be mediated by task cue- or item-triggered priming of a context-sensitive control setting. This lack of transfer to other tasks also fits with cognitive training studies demonstrating that switch costs decrease over training when the same tasks are used, but substantial costs reemerge when participants are confronted with new tasks to switch between (Sabah et al, 2019, 2021). With respect to theories on relative levels of task-set activation, Siqi-Liu and Egner (2020) suggest that less activation (and shielding) of both task sets is more likely than increased activation of both task sets to explain the switch probability effect.…”
Section: Switching-induced Flexibilitysupporting
confidence: 74%
“…Two recent (short-term) cognitive training studies furthermore emphasize the importance of differentiating between task-specific and more general cognitive flexibility (Sabah et al, 2019(Sabah et al, , 2021. These studies suggest that task-specific flexibility can in fact result in increased task shielding and as a consequence reduced flexibility for new tasks (Sabah et al, 2019(Sabah et al, , 2021. In Sabah et al (2019), the authors showed that extended training of switching between the same two tasks and stimuli-while keeping the probability of a switch constant-leads to a reduction in switch costs between these tasks.…”
Section: Facets Of Cognitive Flexibilitymentioning
confidence: 99%
“…Failing to appropriately adapt to cognitive demand-an inability to monitor or anticipate demand, the same lines, it is interesting to consider our results from a "cognitive training" perspective (e.g., Karbach & Kray, 2009;Sabah et al, 2019). A recent study (Sabah et al, 2020), for instance, found increased content variability improved task switching training and including interference (i.e., bivalent stimuli) promoted higher transfer gains, in terms of switching efficiency, as compared with a previous study (Sabah et al, 2019). From this perspective, one might have expected that training participants with high-demand task-repetitions would have improved performance on repetitions, increasing subsequent switch costs.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, Dreisbach and Wenke (2011), suggested that abstract learning (high-order as opposed to S-R mapping rules) supports transfer to different contexts. Further support for these notions is found in Sabah et al's works (Sabah et al, 2019(Sabah et al, , 2020, showing that when relatively more abstract learning is required (by means of hindering concrete learning), greater transfer gains are observed.…”
Section: Discussionmentioning
confidence: 83%